The Use of Metabolomic Tool in Assessing Environmental Exposure - Michele Polyana Rocha Mendes; Leiliane Coelho Andre (International Journal of Occupational and Environmental Medicine, 2021)
The impact of the environment on the development of non-communicable chronic diseases has gained prominence in recent years. In this context, a new chemical exposure assessment strategy is needed that is capable of revealing multiple exposures, as well as reflecting the cumulative interaction between such environmental contaminants in the biological system. From this perspective, metabolomics emerges as a promising tool in this field of knowledge, since it is able to identify changes in metabolism and/or gene expression resulting from exposure to environmental factors. The aim of this study was to describe important concepts, as well as the steps that permeate the metabolomics analysis, and also to present some relevant works with the application of metabolomics in the assessment of chemical exposure. A literature review showed a significant increase in the use of metabolomics in environmental toxicology in recent years. This increase is mainly due to advances in analytical techniques and the improvement of data processing tools. However, this field of investigation remains little explored, especially with regard to the study of toxicity associated with chronic exposure to low levels of chemical agents. Thus, it is urgent that omic biomarkers can be used as a tool for decision-making, especially with a view to protecting, diagnosing and recovering human health.
Keywords: metabolomic